Molecular Differences Between Human Thyroid Follicular Adenoma and Carcinoma Revealed by Analysis of a Murine Model of Thyroid Cancer - Sponziello, Marialuisa (Endocrine Society, 2013)
Mouse models can provide useful information to understand molecular mechanisms of human tumorigenesis. In this study, the conditional thyroid mutagenesis of Pten and Ras genes in the mouse, which induces very aggressive follicular carcinomas (FTCs), has been used to identify genes differentially expressed among human normal thyroid tissue (NT), follicular adenoma (FA), and FTC. Global gene expression of mouse FTC was compared with that of mouse normal thyroids: 911 genes were found deregulated ± 2-fold in FTC samples. Then the expression of 45 deregulated genes in mouse tumors was investigated by quantitative RT-PCR in a first cohort of human NT, FA, and FTC (discovery group). Five genes were found significantly down-regulated in FA and FTC compared with NT. However, 17 genes were found differentially expressed between FA and FTC: 5 and 12 genes were overexpressed and underexpressed in FTC vs FA, respectively. Finally, 7 gene products, selected from results obtained in the discovery group, were investigated in a second cohort of human tumors (validation group) by immunohistochemistry. Four proteins showed significant differences between FA and FTC (peroxisomal proliferator-activated receptor-γ, serum deprivation response protein, osteoglycin, and dipeptidase 1). Altogether our data indicate that the establishment of an enriched panel of molecular biomarkers using data coming from mouse thyroid tumors and validated in human specimens may help to set up a more valid platform to further improve diagnosis and prognosis of thyroid malignancies.